How do Different Surgical Techniques for Cataract Removal Impact Quality of Life And Functional Vision in Elderly Patients? : A Systematic Review - Roysam Azmal sitanggang; Sita Pradjnadewi (The Indonesian Journal of General Medicine, 2025)
Introduction: Age-related cataracts significantly impair vision and diminish the quality of life in elderly individuals worldwide. Cataract surgery is the primary intervention to restore vision and improve daily functioning, but the variety of surgical techniques and intraocular lens (IOL) options necessitates understanding their impact on patient outcomes. This systematic review evaluates the impact of different cataract surgery techniques on the quality of life and functional vision of elderly patients, synthesizing evidence from recent clinical trials and observational studies to identify optimal surgical approaches. Methods: This systematic review adhered to the PRISMA 2020 guidelines. We included studies focusing on patients aged 60 and older with age-related cataracts, evaluating surgical techniques like phacoemulsification, MSICS, or ECCE. Eligible studies were primary research (RCT, cohort, case-control) or systematic reviews/meta-analyses, measuring both quality of life and functional vision outcomes with at least a 3-month follow-up. Data extraction by a large language model focused on study design, setting, participant demographics, surgical technique, and visual performance/quality of life outcomes. The search strategy utilized Boolean MeSH keywords across databases like PubMed, Semantic Scholar, Springer, and Google Scholar. Results: Out of 1538 initial records, 14 studies were included. Visual acuity improved in 13 out of 14 studies, with 10 showing statistically significant improvement. All 14 studies reported improved functional vision or patient-reported outcomes, with 10 achieving statistical significance. Six studies found significant quality of life improvement after intervention. Comparisons revealed no significant difference between femtosecond laser-assisted and standard phacoemulsification, while multifocal/trifocal IOLs improved intermediate/near vision but increased dysphotopsia. Second eye surgery showed additional gains. MSICS was found to be cost-effective with comparable outcomes to phacoemulsification in resource-limited settings. Active-fluidics systems may offer faster early recovery. Discussion: The studies consistently show significant improvements in visual function and quality of life across various cataract surgery techniques, including phacoemulsification and MSICS. Second eye surgery further amplifies these benefits, encompassing socioemotional well-being. While advanced technologies like femtosecond laser-assisted phacoemulsification offer precision, they may not yield significantly better clinical or quality of life results compared to standard methods. The choice of IOL significantly impacts vision, with multifocal and trifocal lenses improving intermediate and near vision but potentially increasing dysphotopsia. MSICS provides a cost-effective alternative in certain settings , and active-fluidics systems may enhance early recovery. Patient-reported outcomes are crucial for capturing the real-world impact of surgery. Conclusion: Cataract surgery is highly effective in restoring vision and enhancing quality of life for elderly patients, with consistent improvements across various techniques. Phacoemulsification remains widely adopted, and advanced IOLs expand visual optimization. Bilateral surgery maximizes functional and emotional gains. Cost-effectiveness of MSICS and the promise of emerging technologies like active-fluidics systems underscore the need for individualized care based on patient needs, cost, and potential side effects.